Isolation and comparative proteomic analysis of mitochondria from the pulp of ripening citrus fruit. (1st February 2021) - Li, Xin; Chai, Yingfang; Yang, Hongbin; Tian, Zhen; Li, Chengyang; Xu, Rangwei; Shi, Chunmei; Zhu, Feng; Zeng, Yunliu; Deng, Xiuxin; Wang, Pengwei; Cheng, Yunjiang
Abstract: Mitochondria are crucial for the production of primary and secondary metabolites, which largely determine the quality of fruit. However, a method for isolating high-quality mitochondria is currently not available in citrus fruit, preventing high-throughput characterization of mitochondrial functions. Here, based on differential and discontinuous Percoll density gradient centrifugation, we devised a universal protocol for isolating mitochondria from the pulp of four major citrus species, including satsuma mandarin, ponkan mandarin, sweet orange, and pummelo. Western blot analysis and microscopy confirmed the high purity and intactness of the isolated mitochondria. By using this protocol coupled with a label-free proteomic approach, a total of 3353 nonredundant proteins were identified. Comparison of the four mitochondrial proteomes revealed that the proteins commonly detected in all proteomes participate in several typical metabolic pathways (such as tricarboxylic acid cycle, pyruvate metabolism, and oxidative phosphorylation) and pathways closely related to fruit quality (such as γ-aminobutyric acid (GABA) shunt, ascorbate metabolism, and biosynthesis of secondary metabolites). In addition, differentially abundant proteins (DAPs) between different types of species were also identified; these were found to be mainly involved in fatty acid and amino acid metabolism and were further confirmed to be localized to the mitochondria by subcellular localization analysis. In summary, the proposed protocol for the isolation of highly pure mitochondria from different citrus fruits may be used to obtain high-coverage mitochondrial proteomes, which can help to establish the association between mitochondrial metabolism and fruit storability or quality characteristics of different species and lay the foundation for discovering novel functions of mitochondria in plants.